Urbanization And Future Of Cities In Africa: The Emerging Facts And Challenges To Planners (Global Journal of Human-Social Science, 2012)
This article unveils the circumstances surrounding urbanization and city development in Africa With histo-demographic antecedents as background and specific examples from different parts of the continent the article describes the trend reasons pattern and consequences of city development in Africa It opines that the future of African cities may not be bleak as orchestrated by a certain school of thought if the planning and management of physical environment is made to curtail urban sprawl and encourage a system of moderate-sized urban centres and urban villages with relatively diversified rural or semi-urban economies and if the urban economy of the continent is made to be less marginalized in the global economy
Keywords: Urbanization; histo-demographic; sprawl; marginalized